Engendering support: Hostile sexism predicts voting for Donald Trump over Hillary Clinton in the 2016 U.S. presidential election. (June 2019) - Ratliff, Kate A.; Redford, Liz; Conway, John; Smith, Colin Tucker
This research investigated the role of gender attitudes in the United States 2016 presidential election between Hillary Clinton and Donald Trump. The results of three studies (combined N = 2, 816) showed that, as expected, Trump voters were higher in hostile and benevolent sexism than were Clinton voters. Even after controlling for political ideology and gender (Studies 1, 2, and 3) and minority group attitudes (Study 3), greater hostile sexism predicted more positive attitudes toward Trump, less positive attitudes toward Clinton, and retrospective reports of having voted for Trump over Clinton (Studies 2 and 3). Benevolent sexism did not predict additional variation in voting behavior beyond political ideology and hostile sexism. These results suggest that political behavior is based on more than political ideology; even among those with otherwise progressive views, overtly antagonistic views of women could be a liability to women—and an asset to men—running for office.